The real versus the financial economy: A global tale of stability versus volatility - Simone Alfarano; Niels Förster; Mishael Milaković; Philipp Mundt (Kiel Institute for the World Economy (IfW), 2013)
The question how the real and the financial side of a capitalist economy relate to each other has been a frequently recurring topic in the history of economic thought. Our paper addresses this question from the viewpoint that capital ultimately seeks returns from its perpetual reallocation and essentially faces two choices: it can either be entrepreneurially allocated to real economic activity, or it can be financially invested in legal claims against such activity. Adopting such a perspective, we study here how real and financial returns relate to each other over the past fifteen years, both within and across countries, by considering more than 30,000 publicly traded firms in more than forty countries that stand for 70% of the global population and about 90% of world income. We compare the average rates of return to both types of investment and their respective volatilities. While average returns, perhaps somewhat surprisingly, turn out to be roughly equal across the two domains, the volatility of financial returns exceeds real volatility by an order of magnitude. From a systemic point of view, these findings raise the question why capital would seek out financial investments in the first place.
Keywords: D21; L10; G14; F01; 330; Profit rates; growth rates of market value; excess volatility